Optimized algorithm for speed‐of‐sound‐based infant sulfur hexafluoride multiple‐breath washout measurements - Wyler, Florian; Manogaran, Thuvarakha; Monney, Nathalie; Salem, Yasmin; Steinberg, Ruth; Kentgens, Anne‐Christianne; Jacobs, Carvern; Chaya, Shaakira; Sena, Carla Rebeca da Silva; Künstle, Noëmi; Gorlanova, Olga; Yammine, Sophie; et al. (Pediatric pulmonology, 2024)
Introduction Major methodological issues with the existing algorithm (WBreath) used for the analysis of speed‐of‐sound‐based infant sulfur hexafluoride (SF6) multiple‐breath washout (MBW) measurements lead to implausible results and complicate the comparison between different age groups and centers. Methods We developed OASIS—a novel algorithm to analyze speed‐of‐sound‐based infant SF6 MBW measurements. This algorithm uses known context of the measurements to replace the dependence of WBreath on model input parameters. We validated the functional residual capacity (FRC) measurement accuracy of this new algorithm in vitro, and investigated its use in existing infant MBW data sets from different infant cohorts from Switzerland and South Africa. Results In vitro, OASIS managed to outperform WBreath at FRC measurement accuracy, lowering mean (SD) absolute error from 5.1 (3.2) % to 2.1 (1.6) % across volumes relevant for the infant age range, in variable temperature, respiratory rate, tidal volume and ventilation inhomogeneity conditions. We showed that changes in the input parameters to WBreath had a major impact on MBW results, a methodological drawback which does not exist in the new algorithm. OASIS produced more plausible results than WBreath in longitudinal tracking of lung clearance index (LCI), provided improved measurement stability in LCI over time, and improved comparability between centers. Discussion This new algorithm represents a meaningful advance in obtaining results from a legacy system of lung function measurement by allowing a single method to analyze measurements from different age groups and centers.